Impaired Fibrinolytic Capacity Predisposes for Recurrence of Venous Thrombosis - Korninger, C; Lechner, K; Niessner, H; Gössinger, H; Kundi, M (Thrombosis and Haemostasis, 1984)
The fibrinolytic capacity of 121 patients with a history of venous thrombosis and/or pulmonary embolism was studied by venous occlusion technique, at earliest 3 months after the last thromboembolic episode. After discontinuation of oral anticoagulation treatment the clinical course of the patients was followed and new thromboembolic episodes were noted. During the observation period of 56 ± 18.8 months 45 of 121 patients experienced recurrence of thrombosis. The recurrence-rate was significantly lower in patients with a post-occlusion ELT shorter than 60 min (4.8%/year) than in patients with an ELT longer than 60 min (10.3%/year). It is concluded that the fibrinolytic capacity is a useful parameter for determining the risk of recurrence in patients with venous thrombosis.
Keywords: Tissue-type plasminogen activator; Fibrinolytic capacity-venous thrombosis; Recurrence